2022
DOI: 10.3390/cancers14205124
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Epithelial-to-Mesenchymal Transition and Chemoresistance in Advanced Retinoblastoma Tumors Is Driven by miR-181a

Abstract: Advanced retinoblastoma (Rb) tumors display high metastatic spread to distant tissues, causing a potent threat to vision and life. Through transcriptomic profiling, we discovered key upregulated genes that belonged to the epithelial–mesenchymal transition (EMT) and chemotherapy resistance pathways in advanced Rb tumors. Through in vitro models, we further showed that Rb null tumor cells under prolonged chemo drug exposure, acquires a metastasis-like phenotype through the EMT program mediated by ZEB1 and SNAI2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…However, other genes in the ceRNA network were found to be involved in EMT-related pathways. Has-miR-181a-5p drove EMT in advanced retinoblastoma to enhance its invasion and migration [ 48 ]. ESM1 accelerates cervical cancer cell proliferation and migration by promoting EMT progression [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other genes in the ceRNA network were found to be involved in EMT-related pathways. Has-miR-181a-5p drove EMT in advanced retinoblastoma to enhance its invasion and migration [ 48 ]. ESM1 accelerates cervical cancer cell proliferation and migration by promoting EMT progression [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of miRNA is closely related to the prognosis of tumor metastasis. Vishnu Suresh Babu et al revealed that miR-181a promoted epithelial-mesenchymal transition and chemotherapy resistance in advanced-stage retinoblastoma [15]. Elena Andreucci et al [16] elaborated the role of miR-214 in tumor metastasis caused by immune cell abnormalities, and these novel functions have attracted significant attention.…”
Section: Discussionmentioning
confidence: 99%
“…(Fig. 3) which may have an impact on the oncogenic properties of retinoblastoma through multiple mechanisms, including the acquisition of stem cell-like phenotype, EMT activation and metabolic rewiring [20][21][22][23].…”
Section: Signalling Pathways Involved In Retinoblastomamentioning
confidence: 99%
“…These belong to an oncogenic network that promotes phenotypic and molecular changes in cellular state to adapt retinoblastoma to extracellular stress and drug treatment. As described below, such pathways may lead to EMT activation [ 20 ], undifferentiated stem-like cellular state [ 21 ], or glycolytic shift towards OXPHOS to alternate energy fuels and metabolic routes depending on the need of tumor cells [ 22 , 23 ]. The deep understanding of the mechanism underlying cell plasticity in retinoblastoma may provide insights for establishing new therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%